Dual embryonic origin of maxillary lateral incisors: clinical implications in patients with cleft lip and palate - Garib,Daniela Gamba (2015)
Introduction:Cleft lip and palate are craniofacial anomalies highly prevalent in the overall population. In oral clefts involving the alveolar ridge, variations of number, shape, size and position are observed in maxillary lateral incisors. The objective of this manuscript is to elucidate the embryonic origin of maxillary lateral incisors in order to understand the etiology of these variations.Contextualization: The hypothesis that orofacial clefts would split maxillary lateral incisor buds has been previously reported. However, recent studies showed that maxillary lateral incisors have dual embryonic origin, being partially formed by both the medial nasal process and the maxillary process. In other words, the mesial half of the lateral incisor seems to come from the medial nasal process while the distal half of the lateral incisor originates from the maxillary process. In cleft patients, these processes do not fuse, which results in different numerical and positional patterns for lateral incisors relating to the alveolar cleft. In addition to these considerations, this study proposes a nomenclature for maxillary lateral incisors in patients with cleft lip and palate, based on embryology and lateral incisors position in relation to the alveolar cleft.Conclusion:Embryological knowledge on the dual origin of maxillary lateral incisors and the use of a proper nomenclature for their numerical and positional variations renders appropriate communication among professionals and treatment planning easier, in addition to standardizing research analysis.